Particle Tracking Model Approach for Analyzing Crude Oil Spill (Palm Fatty Acid Distillate) in Bayur Bay Based on Navier Stokes Discrete - Koko Ondara; Ulung Jantama Wisha; Serli Marlinda Panjaitan (Universitas Diponegoro, 2021)
Oil spilled in the marine ecosystem may be induced by some sources which alter over time and location. Oil leakage from offshore oil drilling, underwater oil pipeline leakage, etc., are the possible source of oil spill pollution. Marine pollution generated by oil spilling occurred in Padang City in 2017. Palm Fatty Acid Distillate (PFAD) spilled within Bayur Bay Harbor due to a leaking storage tank. As much as 50 tons of PFAD overflowed and commenced to pollute Bayur coastal bay. This study aimed to determine the distribution pattern of oil spills throughout the Bayur Bay based on a hydrodynamical model. We employed some oceanographic data and PFAD characteristics obtained directly from survey results. We simulated the particle tracking model for 30 days since the PFAD spilled within the port. The model developed applied the Least Square method to analyze tidal data and a flexible mesh as a model basis, while the governing equation used is Navier Stoke discrete. During a month of simulation, the dominant particles' distribution is still spinning around the Bayur Bay due to the weak current characteristics with the magnitude ranging from 0.02-0.06 m/s. The lighter PFAD particle mass tended to move faster throughout the bay and settled in the coastal area. It will pollute the coastal system even though it is going to be decomposed chemically in the sediment.